PENINGKATAN KEKERASAN DAN KETAHANAN AUS BAJA KARBON RENDAH DAN BESI COR KELABU MELALUI PROSES VANADISASI - Lukito Dwi Yuono (Universitas Muhammadiyah Metro, 2015)
The surface hardening process is one of the high temperature treatment processes wich is applied only on the surface of the object of the treatment so that it result an object with superficial hardness without changing the interior matrix shape of the object. The materials used in this research are Perlitics Gray Cast Iron and Low Carbon Steel which are easily avaliable in the market) to increase the hardness and resistance of the surface of the object through vanadisation. As the diffusion material, vanadium, which was derived from ferro vanadium powder was used. The experiment was conducted by varying temperatures of 800 oC and 875 oC, with the resisting periods of 1 hour, 3 hours, and 5 hours. From this experiment, it was expected that there was anincrease in hardness and resistance of the object surface without changing its interior matrix shape. After conducting the experiment and some test namely metallography test, hardness test, and resistance test, it showed that there was diffusion process on the surface of the object. Having been compared with the sample before the treatment, it can be seen that : 1. Based on the result of metallography test, there is a change in the exterior shape of the sample, but a constant interior matrix shape of it. 2. Based on the hardness test, there is an increase on hardness, maximally on the sample caded BCK-5/875 to the rate of 742 HV. 3. Bases on the resistance test, there is an increase also in its rate. It can be seen from the lowest weight loss rate on the sample coded BCK-5/875 to 0,0018 gr.